Unobtrusive Movement Detection during Sleep based on Load Cell Dynamics - Adami, Adriana Miorelli; Adami, André Gustavo; Hayes, Tamara; Beattie, Zachary (Anais do Simpósio Brasileiro de Computação Aplicada à Saúde (SBCAS); 2013: Anais do XIII Workshop de Informática Médica, 2013)
Changes in the pattern of motor activities during sleep can be a disease marker, or can reflect various abnormal physiological and neurological conditions. Currently, there are no unobtrusive ways to assess the quality of sleep at point of care outside of a clinic. In this paper, we propose an alternative method of detecting movements during sleep that can be deployed unobtrusively in a patient’s own home by using load cells sensors. This subject-independent method uses a linear discriminant function to detect periods of movement in a cohort of 17 patients admitted to a sleep lab. The system yields a sensitivity of 97.5% and a specificity of 99% when compared to technicians’ annotations.